Ten new poplar cultivars provide laminated veneer lumber for structural application - Rahayu, Istie; Denaud, Louis; Marchal, Rémy (Annals of Forest Science, 2014)
International audience Key message Lambro, Brenta, Taro, Alcinde and Soligo are new poplar cultivars suitable for laminated veneer lumber (LVL) for structural purposes. While Lena, Koster, Dvina, Mella and Trichobel must be used with careful veneer material selection to obtain high value of mechanical properties. Context In France, the veneer processing industry uses only a very small number of different poplar cultivars. Aims This paper set out to investigate the potential of laminated veneer lumber made from 14 new cultivars for structural purposes, with a focus on juvenility and veneer thickness effects. Methods The mechanical properties of laminated veneer lumber panels made from each cultivar (114 samples per cultivar) were characterized by measuring their density, modulus of elasticity and modulus of rupture. Results A tight correlation was found between destructive and non-destructivemodulus of elasticity tests (R2=0.90, 1,808 samples). Five cultivars had suitable mechanical properties for structural applications ('Lambro', 'Brenta', 'Taro', 'Alcinde' and 'Soligo'). Five cultivars needed to be used with careful sample selection ('Lena', 'Koster', 'Dvina', 'Mella' and 'Trichobel'), and the final four ('I214', 'A4A', 'Triplo' and 'Polargo') could not be recommended for structural purposes. Conclusion The advantage of using veneers of mature wood compare to juvenile wood for laminated veneer lumber (LVL) production was due to an improvement of modulus of elasticity and modulus of rupture in the range of 15 to 20 %. The use of thick veneers (5.25 mm compared to 3 mm) did not appear to be detrimental to laminated veneer lumber mechanical performance.